Manajemen Homestay Berbasis Syariah Sebagai Upaya Pengembangan Pariwisata Halal dan Ekonomi Kreatif - Dewi, Novi Yanti Sandra; Hulaimi, Ahmad; Wahab, Abdul (Al-Fikru: Jurnal Ilmiah, 2022)
Halal tourism is a new phenomenon in the tourism industry. The demands of Muslim tourists for Muslim-friendly tourist destinations make various tourism supporting sectors including homestays designed with comfortable designs and guaranteeing Muslim tourists can carry out worship in them. In this regard, this study highlights the potential of homestays in Mandalika as the host of international motor racing events. But unfortunately the homestay is still simple, and does not have a systematic management, which has an impact on tourist satisfaction. This study aims to analyze sharia-based homestay management in the Mandalika Circuit area. This research uses a qualitative research method based on phenomenology. Informants in this study are homestay managers around the Mandalika Circuit. Data analysis used the Miles and Huberman technique, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the study explain that (1) there is still a lack of understanding by managers about sharia management so that the business has not run optimally, (2) the applied sharia management includes several aspects, namely planning, organizing, controlling, Leading.